Evaluación de los gases de combustión del proceso de secado, utilizando cascarilla de arroz y lignito en la planta de cementos Selva S.A - Chávez Cabrera, Alcidia (2010)
The present study aims to assess the gases emitted by burning rice husk in the drying process in the factory of Cementos Selva SA, during the months of December 2009, January, February and March 2010, taking into account the importance of involving the use of this by-product that eliminates toda y through open burning, which results in energy losses, as well as the emission of several pollutants. As for the measurements of concentrations of combustion gases, these were made with a frequency of once a week, at random, where the Continuous Emissions Monitoring (CEM), was conducted over a total period of 60 minutes, time intervals of 15 minutes, obtaining concentrations of the gases carbon monoxide (CO), nitrogen oxides (NOx) and sulfur dioxide (S02), which when contrasted with the permissible limits (MPL) of legislation environmental legislation, and through the use of a statistical test, it was determined that fall below the LMP. During the stage of field study was conducted activities such as measuring the moisture content of rice husks, before entering the combustion chamber, giving mínimum and maximum values ranging between 9.48% and 20.94% respectively, were likewise measurements of the calorific value of husk which resulted in values between 293 7 kcal 1 kg and 3328 Kcal 1 kg and for the implementation of these activities were used environments and procedures, the quality controllaboratory, located within the premises of plant of Cementos Selva SA The temperature of the combustion chamber was recorded on the control panel of the dryer area, ranging from 176 o C and 679 o C, these temperatures affect the concentrations of combustion gases emitted into the environment. In addition to the stage of cabinet was used meteorological data such as temperature and relative humidity recorded by the Vantage Pro 2 and provided by the company, data that were used for sorne comparisons.